Performance of technical implementation officers (PPTK) in construction services at the education department of Banjar district - Mahriansyah,; Mursadin, Aqli (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
In 2022, the Facilities and Infrastructure Division of the Banjar Regency Education Office completed 118 Physical Work Packages, including planning and supervision. The Technical Implementation Officers (PPTK) in Construction Services at the Banjar Regency Education Office face significant challenges due to the complexity of their responsibilities and the mismatch between employee competencies and their respective positions. This study aims to assess the performance level of PPTK in Construction Services, identify key influencing factors, and propose strategies for improvement. The research employs validity and reliability tests using Cran R, followed by Customer Satisfaction Index (CSI) analysis and Importance Performance Analysis (IPA) to determine priority indicators requiring attention. The study concludes that an appropriate strategy for improving PPTK performance involves ensuring that officers possess relevant educational qualifications to enhance their effectiveness in managing construction projects and avoiding failures.